2016
DOI: 10.1038/srep38631
|View full text |Cite
|
Sign up to set email alerts
|

Aldosterone induces rapid sodium intake by a nongenomic mechanism in the nucleus tractus solitarius

Abstract: The purpose of this study was to determine whether aldosterone has a rapid action in the nucleus tractus solitarius (NTS) that increases sodium intake, and to examine whether this effect of aldosterone, if present, is mediated by G protein-coupled estrogen receptor (GPER). Adult male Sprague-Dawley rats with a stainless-steel cannula in the NTS were used. Aldosterone was injected into the NTS at the doses of 1, 5, 10 and 20 ng 0.1 μl−1. A rapid dose-related increase of 0.3 M NaCl intake was induced within 30 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 53 publications
(70 reference statements)
1
14
0
Order By: Relevance
“…Although we know that HSD2 neurons regulate sodium appetite (Jarvie and Palmiter, 2017;Resch et al, 2017), our observation that non-HSD2 neurons also showed c-Fos expression raises the possibility that other neurons participate as well. Aldosterone could affect these neurons via G protein-coupled estrogen receptor (GPER) (Funder, 2011;Qiao et al, 2016). Alternatively, non-HSD2 neurons could be activated synaptically by HSD2 neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Although we know that HSD2 neurons regulate sodium appetite (Jarvie and Palmiter, 2017;Resch et al, 2017), our observation that non-HSD2 neurons also showed c-Fos expression raises the possibility that other neurons participate as well. Aldosterone could affect these neurons via G protein-coupled estrogen receptor (GPER) (Funder, 2011;Qiao et al, 2016). Alternatively, non-HSD2 neurons could be activated synaptically by HSD2 neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, preclinical data in rats suggest that aldosterone levels are elevated after menopause and that estrogen therapy can limit this increase (Macova et al, 2008; Wang et al, 2013), but such results appear to be in conflict with clinical observations that post‐menopause hormone replacement therapy increases the aldosterone/renin ratio (Ahmed et al, 2017). Nevertheless, the GPER is reportedly responsible for some of the mineralocorticoid receptor‐independent effects of aldosterone (Evans, 2019; Gros et al, 2011, 2013; Qiao et al, 2016), but there is debate as to whether aldosterone can directly bind to the GPER (Cheng et al, 2014). Aldosterone was recently reported to increase mRNA expression of CYP11B2, that is, aldosterone synthase, via GPER in aldosterone‐producing adenomas obtained from patients with primary aldosteronism (Caroccia et al, 2019).…”
Section: Agonists and Antagonists Of Gpermentioning
confidence: 99%
“…To our knowledge, there are only a couple of areas in the brain in which the MR and 11β-HSD2 are co-expressed resulting in a high selectivity for aldosterone action on the MR. These are mainly the nucleus of the solitary tract (NTS), which could be shown to play an important role for salt intake under aldosterone stimulation [37,43,[45][46][47]. In this context brain-specific knockout of 11β-HSD2 was shown to increase sodium intake in mice, which suggests that under these conditions salt appetite may also be regulated by glucocorticoids [48].…”
Section: Does Aldosterone Impact Dietary Salt Intake?mentioning
confidence: 99%